Robert Adam's London - Sands, Frances (Archaeopress, 2016)
The iconic eighteenth-century architect Robert Adam was based in London for more than half of his life and made more designs for this one city than anywhere else in the world. This work review a wide variety of his designs for London, highlighting lesser-known buildings as well as familiar ones.